2002
DOI: 10.1002/ptr.867
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of plumbagin derivatives and their inhibitory activities against Ehrlich ascites carcinoma in vivo and Leishmania donovani Promastigotes in vitro

Abstract: Plumbagin, a plant-derived bioactive naphthoquinonoid compound, was converted to a hydroquinonoid derivative, which was studied for its tumour-inhibitory and antileishmanial activities for the first time. A similar chemical transformation was undertaken on an analogous dimeric compound, diospyrin, and its bioassay results were compared with those of the plumbagin derivative. Synthesis of the derivative of plumbagin did not result in a marked enhancement of the tumour-inhibitory activity, whereas the improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
50
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 12 publications
0
50
0
Order By: Relevance
“…The stereochemistry at the C-24 asymmetric centre was investigated by a careful comparison with the 1 H NMR spectra of both epimers at C-24 in similar steroids (Gamze et al 2002). The steroid was obtained as colourless crystals (13 mg Though compounds 1 and 2 have been reported elsewhere in literature (Dey & Harbone 1991, Hazra et al 2002, this is the first time they are being reported from the Plumbago species growing in Kenya.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The stereochemistry at the C-24 asymmetric centre was investigated by a careful comparison with the 1 H NMR spectra of both epimers at C-24 in similar steroids (Gamze et al 2002). The steroid was obtained as colourless crystals (13 mg Though compounds 1 and 2 have been reported elsewhere in literature (Dey & Harbone 1991, Hazra et al 2002, this is the first time they are being reported from the Plumbago species growing in Kenya.…”
Section: Resultsmentioning
confidence: 82%
“…-This was obtained from fraction Fr 12-34 and identified from 1D and 2D NMR data, mass spectral data and by comparing these spectroscopic data with those reported in literature. Plumbagin (Figure) was obtained as bright yellow needles (401 mg), mp 77.8-77.4°C [literature value 76.8-77.4°C (Dinda et al 1998, Hazra et al 2002 -6-methylheptan-2-yl)-10,13-dimethyl-2,3,4,7,8,9,11,12,14,15,16,17-dodecahydro-1H-cyclopenta[a]phenanthren-3-ol (β-Sitosterol) -This compound (Figure) was identified by comparing the spectral data obtained with those reported in the literature (Dey & Harbone 1991). The stereochemistry at the C-24 asymmetric centre was investigated by a careful comparison with the 1 H NMR spectra of both epimers at C-24 in similar steroids (Gamze et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Plumbagin has been shown to exert anticancer and antiproliferative activities in animal models as well as in cells in culture (7)(8)(9)(10)(11). Sugie et al (12) have shown that plumbagin significantly inhibited azoxymethane-induced intestinal carcinogenesis in rats, suggesting its chemopreventive activity (12).…”
mentioning
confidence: 99%
“…The cytotoxic action of plumbagin in keratinocytes and cervical cancer cells was found to be due to a change in the redox status of the cell (6,15). In embryonic kidney and brain tumor cells, plumbagin inhibited the enzyme NAD(P)H oxidase (16), linked with anticarcinogenic (7)(8)(9)(10)(11)(12) and atherosclerotic effects (17). Besides anticancer effects, plumbagin also exhibited radiosensitizing properties in experimental mouse tumors as well as in tumor cells in vitro (18 -20).…”
mentioning
confidence: 99%
“…Quinones, in general, and, particularly hydroxyquinones, as well as their reduced derivatives, have been tested against several parasite species (Croft et al 1992, Sauvain et al 1993, Iwu et al 1994, Ray et al 1998, Kayser et al 2000, Ferreira et al 2002, Hazra et al 2002 and low bioavailability (Kayser et al 2000). Atovaquone, a hydroxynaphtoquinone, showed to have a concentration-dependent in vitro activity against L. infantum (Jernigan et al 1996), while the in vivo activity in a murine model remained low (Murray et al 1996, Cauchetier et al 2000.…”
mentioning
confidence: 99%